2015
DOI: 10.3329/cmoshmcj.v14i1.22871
|View full text |Cite
|
Sign up to set email alerts
|

Audit on the Management of Bronchiolitis: A Single Centre Real World Experience in Bangladesh Can We do Better ?

Abstract: Background: Bronchiolitis is the most common reason for hospitalization of children in many countries.Though Respiratory Syncytial Virus (RSV) is the most common organism causing bronchiolitis, but antibiotics are used widely.So the aim of the present study is to establish whether antibiotic has any role in bronchiolitis management along with supportive treatment. Methods:This retrospective study included 100 infants and children between 2-24 months of age admitted with clear cut sign symptoms of bronchiolitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…The residence of bronchiolitis children in present study was commonly urban. This finding is consistent with results of Hamid et al (11) study in Bangladesh and attributed this difference to air pollution and crowding environment in urban areas. The family history of atopy was relatively high among children with bronchiolitis.…”
Section: Discussion:-supporting
confidence: 93%
“…The residence of bronchiolitis children in present study was commonly urban. This finding is consistent with results of Hamid et al (11) study in Bangladesh and attributed this difference to air pollution and crowding environment in urban areas. The family history of atopy was relatively high among children with bronchiolitis.…”
Section: Discussion:-supporting
confidence: 93%
“…A study by Kabir AL et al 16 also found that pneumonia was treated mostly with ceftriaxone in 47.5% cases followed by other antibiotics. In this study, most common antibiotics used for the treatment bronchiolitis was ceftriaxone in 25% cases followed by other antibiotics; but different studies by Hamid F et al 23 and Kabir AL et al 16 do not support the routine use of antibiotics in the treatment of bronchiolitis. Antibiotic should be considered only when there is evidence of secondary bacterial infection.…”
Section: Discussioncontrasting
confidence: 55%
“…They also determined to difference in terms of clinical outcomes and lengths of hospital stay. Hamid et al 19 examined 100 patients with acute viral bronchiolitis in a retrospective study. No positive contribution to healing at clinical follow-up or significantly significant difference in length of hospital stay was observed between the group using iv or oral antibiotics and the no antibiotic group.…”
Section: Discussionmentioning
confidence: 99%